Pengenalan Kewirausahaan Bagi Pelajar - Nurmiati Irvan; Fina Diana; Murbayani Murbayani; Ridwan Ridwan; Ilham Ilham; Irwan Syarif (Universitas Patria Artha, 2022)
Entrepreneurs need to be introduced from an early age to instill an entrepreneurial mentality with the aim of opening students' minds to be able to create their own jobs, because with them entrepreneurship the benefits they get are not only for ourselves but also for others so that it indirectly helps create jobs. to reduce the existing unemployment rate by providing jobs to people around the business being undertaken. Problems faced by partners in community service activities include students not understanding entrepreneurship and students not being interested in the business world, especially entrepreneurship. The expected outcome of this community service activity is that students feel interested in becoming entrepreneurs and grow their creative ideas into positive productivity and provide benefits for students in particular and benefits for the surrounding environment in general. This service stage starts from preparation, implementation of service activities in the form of counseling introduction to entrepreneurship for students and ends with the closing stage. This activity was said to be successful where all participants were present and their enthusiasm and interest was evident, this was evidenced by the presence of several participants who actively asked questions during the discussion session. For this reason, this activity needs to be developed so that it can motivate students to develop their creativity to become young entrepreneurs, so that similar activities can also be carried out in other schools to increase students' knowledge and understanding of entrepreneurship.Keyword: Entrepereneurship, Student, Productivity